TYPES OF HANDMADE DOLLS IN TURKEY - Özdemir, Melda (Journal of Tourism, Sustainability and Well-being, 2018)
Handmade dolls, plastic, wood, glass, ceramic, any mineral, soil, plaster, leather, cloth and so on. They are human form toys made of materials. Handmade dolls art is the world’s oldest hand-crafted art that emerged from the assessment of the increased fragments available to show the future responsibility of the mother of the daughter-in-law.Handmade dolls collectors and decorators do not have any jobs in our society and they have characteristics that appeal to people of all ages. The ornaments that complement the clothing such as dolls, ethnic dolls, different national dresses, necklaces, ear, wrists and necklaces, earrings, bracelets and rings attached to fingers carry all traces of folk culture and art. These dolls, which are produced with different materials under different names in different regions of our country, take their names according to the material they are making and they reflect the characteristics of the area in terms of production and clothes. This study aims to introduce handmade doll varieties which are made in Turkey and are still being made. Doll varieties will be supported by visuals while giving information about the construction techniques to be categorized according to the material used.